Mengapa Influencer Mampu Mendorong Pembelian? Analisis Peran Kepercayaan Merek dan Kesadaran Merek - Meiyana Linda Purwanti; Waluyo Budi Atmoko; Ariefah Yulandari; Yulianto Yulianto (Jurnal Bisnis dan Kewirausahaan, 2025)
Abstract This study aims to analyze the influence of influencers on purchasing behavior through brand trust, brand awareness, and purchase intention among Instagram users in Surakarta City. This study used a quantitative approach with a causal design and a cross-sectoral survey. Data were obtained through an online questionnaire distributed to 200 respondents aged at least 17 years who actively use Instagram. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS and logistic regression. The results showed that influencers have a positive influence on brand trust. Brand trust also has a positive influence on brand awareness and purchase intention, while brand awareness has a positive influence on purchase intention. Furthermore, purchase intention was shown to have a positive influence on purchase behavior. These findings indicate that influencers' effectiveness in driving purchase behavior occurs through increased brand trust, brand awareness, and purchase intention. Therefore, companies need to select credible influencers to improve the effectiveness of their digital marketing strategies.